Influence of liquid phase hydrodynamics on biofilm formation on structured packing: Optimization of surfactin production from Bacillus amyloliquefaciens. (12th October 2017) - Zune, Q.; Telek, S.; Calvo, S.; Salmon, T.; Alchihab, M.; Toye, D.; Delvigne, F.
Abstract: This work gives a useful insight of hydrodynamic aspects within single-species biofilm reactor with metal structured packing and proposes an original methodology based on high energy X-ray tomography to characterize liquid and biofilm distribution. It has been observed that efficiency of initial liquid distribution controls the biofilm distribution within the packing. This parameter mainly depends on the liquid distributor design. The local liquid velocity within the packing element, depending of the recirculation flow rate, the structural properties of the packing and the bed void fraction distribution, have an effect on initial cell attachment and subsequent biofilm growth. However, once started the process efficiency depends mainly on the biofilm spreading on the packing, affecting further liquid distribution. The liquid flow rate is involved in a physicochemical effect leading to foam formation. The latter decreases surfactin recovery in the liquid phase and provokes biofilm detachment of the packing. Thus, the best surfactin yield production, up to 300 mg/L, occurs for a liquid load of 17.6 L/m 2  min supplied by a multiple point source distributor. From a technical point of view, these operating conditions are particularly interesting since foam formation is completely suppressed. Highlights: Biofilm reactors can be used for the production of high-value products. Adherence of B. amyloliquefaciens is influenced by the liquid hydrodynamics. Biofilm formation on packing takes place on the wetted area. Biological factors, such as spreading of the biofilm, must also be considered. Biofilm reactor avoids any technical limitations associated with foam formation.